PERSEPSI MASYARAKAT TERHADAP PELAKSANAAN TRADISI MITONI DIKAMPUNG BUNGARAYA KECAMATAN BUNGARAYA KABUPATEN SIAK - Suntari, Suntari; Erlinda, Sri; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: This research is motivated to explain the people's perceptions of the implementation of the mitoni tradition and the meaning contained in the implementation of this mitoni tradition in Kampung Bungaraya. The formulation of the problem of this research is "What is the public perception of the implementation of the mitoni tradition in Bungaraya Village, Bungaraya District, Siak Regency". The purpose of this study was to determine how people's perceptions of the implementation of the mitoni tradition in Bungaraya Village, Bungaraya District, Siak Regency. Data collection techniques in this study were observation, interviews and documentation. There are 6 informants in this study, namely Dukun Bayi (1 person), Community Leaders (1 person), Mr RT (1 person), Communities who carry out the tradition of mitoni (2 people), and Society who participate in the mitoni tradition (1 person) in the village of Bungaraya. Data analysis techniques in this study used qualitative methods. The results in this study prove that the community's perception of the implementation of the mitoni tradition is still very good, it is evident that the people in Kampung Bungaraya still carry out the mitoni tradition and still maintain the sacred values that exist in the mitoni tradition. The community has the perception that the implementation of the tradition of mitoni as a form of gratitude to Allah SWT who has given a baby and to ask for prayer from Allah SWT so that pregnant women can give birth safely and babies born safely without any deficiencies.Key Words: Community Perception, Mitoni Tradition